Epinephrine adjuvant reduced epidural blood vessel penetration incidence in a randomized, double‐blinded trial. Issue 10 (5th June 2015) - Denny, J. T.; Cohen, S.; Stein, M. H.; Banerjee, T.; Naftalovich, R.; Hunter‐Fratzola, C. W.
<x xml:space="preserve">Abstract</x> Background Accidental intravascular injection is a significant and potentially devastating risk of epidural block, particularly in parturients whose epidural veins are engorged and hence more easily pierced. This prospective randomized, double‐blinded study determined whether the addition of epinephrine to epidural ropivacaine administered by gravity before catheter insertion was associated with fewer epidural catheter blood vessel penetrations. Method Four hundred and two parturient patients receiving epidural block for elective C/S were randomly allocated to two groups; group I (n = 201) received only ropivacaine 0.75% with fentanyl 5 μg/mL, whereas group II (n = 200) also received epinephrine 5 μg/mL. Both groups received a total of 21 mL anesthetic solution in four increment doses of 3, 5, 5, 5 mL by gravity into the needle through a 22 inch extension tubing before insertion of the closed‐end tip catheter. An additional 3 mL of the anesthetic solution was then administered through the catheter. Results Epidural epinephrine adjuvant was associated with fewer epidural vessel penetrations (4% vs. 16.5%, P < 0.0001). The addition of epinephrine also significantly reduced catheter insertion problems (12% vs. 23.5%, P‐value 0.0024) including the need for catheter readjustment (4.5% vs. 16%, P‐value 0.0002) or reinsertion (2.5% vs. 9%, P‐value 0.0054). The addition of epinephrine significantly reduced incidence and severity of sedation and had faster onset of surgical block. Sensory level and overall satisfaction did not differ significantly among the groups. Conclusion The addition of epinephrine to ropivacaine improves the safety and quality of epidural anesthesia when administered by gravity flow via the Hustead needle for cesarean sections.